Formulation development and microstructure analysis of a polymer modified bitumen emulsion road surfacing : a thesis presented in partial fulfilment of the requirements for the degree of Master of Technology in Product Development at Massey University, Palmerston North, New Zealand - Forbes, Allan R (Massey University, 2000)
The purpose of this research was to develop a formulation for a polymer modified bitumen emulsion road surfacing product called microsurfacing to a mid-scale prototype stage. A supplementary part of the development was to investigate the polymer-bitumen interactions and how they affected the products end properties using confocal microscopy. The formulation development consisted of three stages: technical design specifications, initial design, detailed design. The technical specification was developed to define the product performance in quantitative measures, and set the initial formulation parameters to work within. The initial design development screened three polymers, four methods of adding polymer to the emulsion and two grades of bitumen. Experimental design techniques were used to determine the best polymer-bitumen combination and emulsion process method. Further experimental investigations consisted of screening three emulsifiers and assessing the effect of aggregate cleanliness on the surfacing abrasion and curing rate. The detailed design used experimental factorial design to examine the effects of polymer concentration, emulsifier level, and emulsifier pH on the emulsion stability, microsurfacing wear resistance and cure rate. The emulsion residue was observed using confocal microscopy with fluorescence light and the microsurfacing mixture using both fluorescent and reflected light. The research showed that a emulsion using 100 penetration grade Safaniya bitumen with SBR latex polymer post added could provide microsurfacing abrasion resistance of less than 100 g/m 2 ; an improvement of 85% on the minimum specification. The vertical permanent deformation was less than the 10% and could not be attained without polymer addition. The use of aggregate with a high cleanliness and an alkyl amidoamine emulsifier resulted in surfacing cohesion development of 20 kg-cm within 90 minutes, which compares closely to the international specification. Unexpected results not reported before were that the emulsion residue from biphase modified emulsions had a softening point up to 10°C higher than polymer modified hot bitumen with the same polymer concentration. The biphase emulsified binder residue also has a very different microstructure to hot modified bitumen and this structure has been proposed to help account for the improved resistance to high temperature and applied stress. Modifications to the formulation are to improve the emulsion settlement and should focus on the density difference between the bitumen and polymer latex. This research has shown that a microsurfacing reading product can be successfully formulated with New Zealand bitumen and aggregate sources to meet key specified performance requirements. By systematically investigating the effects of materials on the performance properties of the product, a formulation ready for a mid-scale experiment has been proposed.
Keywords: New Zealand; Bituminous materials